Loyal Now Or Loyal Later : Moderating Role Of Satisfaction In Customer Loyalty - Marsudi Marsudi; Sri Nastiti Andharini (Manajemen Bisnis, 2024)
This research is aimed at analyzing the role of customer satisfaction as a moderator of the relationship or influence between product and service quality on customer loyalty. The population in this study was obtained from customers who had enjoyed products and services at the Tenes fried chicken restaurant in Malang city. Sampling used a purposive sampling technique with the criteria that customers were at least 18 years old, had purchased and enjoyed products and services at least three times and lived in the city of Malang. The data collection technique used was by distributing questionnaires to 100 respondents. The data analysis technique in this research used structural equation modeling-partial least squares (SEM-PLS) with the results that service quality and product quality each have a positive and significant effect on customer loyalty, service quality has a negative effect. and significant on customer loyalty which is moderated by customer satisfaction, product quality has a positive and significant effect on customer loyalty which is moderated by customer satisfaction.